State-of-the-art novel catalyst synthesised from waste glassware and eggshells for cleaner fuel production. (15th December 2022) - Al-Muhtaseb, Ala'a H.; Jamil, Farrukh; Osman, Ahmed I.; Tay Zar Myint, Myo; Htet Kyaw, Htet; Al-Hajri, Rashid; Hussain, Murid; Ahmad, Mohammad N.; Naushad, Mu
Graphical abstract: Highlights: A highly efficient novel catalyst (Ce@CaO-SiO2 ) was synthesised. Waste glassware (SiO2 ) was used as a precursor for the catalyst synthesis. The waste eggshell powder was used for modifying SiO2 . Waste beef tallow was used as a source to produce biodiesel as a cleaner fuel. Reusability of synthesised catalyst proved its commercial viability. Abstract: Biodiesel is regarded as an environmentally friendly alternative fuel. The current research synthesises novel heterogeneous catalysts derived from waste (lab glassware and eggshells) and utilised for biodiesel production. Beef fat, abundantly available worldwide, is used as an oil feedstock and then converted into biodiesel, an environmentally friendly fuel. The synthesised catalyst consists of precursor silica dioxide (treated waste glassware) and calcium oxide (calcined from eggshells) that have been modified by impregnating cerium oxide to increase activity. The catalyst is characterised to ensure its suitability for the reaction to produce methyl esters (biodiesel) from animal fat, and biodiesel production is then tested. Characterisation revealed the suitability of the catalyst for the intended application, followed by a comprehensive parametric study to optimise the reaction conditions, including process temperature, time, methanol to oil molar ratio, and catalyst loading. According to the parametric study, the optimal conditions are as follows; process temperature (70 °C), time (100 min.), methanol to oil molar ratio (11) and catalyst loading (3 wt%), where the optimum biodiesel yield was 95.29 wt%. Furthermore, the produced biodiesel is then characterised to report its fuel properties and compared to standards (ASTM6751 & EN14214) which revealed its suitability as a potential alternative fuel. The reusability of the catalyst is also determined. The results indicated that it could be reused up to five times without a noticeable decrease in its reactivity. Based on the results, it can be concluded that synthesised catalysts from such waste materials are a viable option for commercial biodiesel production.